Análise de durabilidade da ponte do Rio do Carmo utilizando ensaios não destrutivos, norma DNIT e a metodologia GDE/UNB - Medeiros, Alisson Gadelha de (2015)
The durability of reinforced concrete structures has motivated many researches, considering the high cost of repairs in many situations, such as bridges, as well as the damage caused by the need to ban regarding recovery services. Thus, this study aims to assess the conditions of durability of the bridge over the Carmo River with 90.90 meters long. This was built in 1976 and is located at km 36 of the BR-110 highway, between the municipalities of Areia Branca/RN and Mossoró/RN, in environmentally high aggression region. For this study, non-destructive tests were done on that proved to be good homogeneity of the concrete before the rebound hammer testing. For ultrasound measures the quality of the concrete was identified as "regular" and enabled the estimation of the dynamic modulus of elasticity and strength of 13.51 MPa and 17.60 GPa, respectively. The carbonation depth assay gave values in steps of 0.00 to 19.00 mm and the testing of the presence of chlorides, there were larger dimensions, most of them being equal to 22.80 mm. However, both did not reach the depth of the steel, 30 mm. The corrosion potential of the test, most of the measurement concentrated in a range of -150 to -250 mV which indicates probabilities of 10 to 90% corrosion. Pathological present manifestations were identified using inspection methods: a standard DNIT 010/2004 and GDE / UnB. With this, from them, it was observed that the highest incidence of injuries suffered were in the superstructure, the mesostructure and other auxiliary elements such as the facade beams. Furthermore, according to this lifting, it was possible to quantify the deterioration of the structure; so that was obtained technical score equal to 3 in accordance with standard DNIT 010/2004, characterizing it as a work "potentially problematic", and overall degree of deterioration of the structure (Gd) equal to 64.03 classifying the level "High". In comparison between both methodologies, the GDE/UnB resulted in greater accuracy, due to richness of detail in your analysis. All these results indicate that the bridge study, needs repairs in the elements studied in this research and allies for more specific inspections, will be able to plan the most appropriate solution in relation to safety aspects and economics.